Parametric study of sliding mode fracture in structural plain cement concrete for various sizes of beams - T, Bhavanichowdary; Padmaja, S.; Saritha, M.; Vinod Kumar, M. (International Journal of Engineering and Technology, 2018)
Fracture mechanics a part of solid mechanics deals with the crack initiation and propagation under certain loading conditions, as we know at ultimate load, the maximum shear stress is relatively larger than the shear strength in existence of compressive stress, which eventually results in shear failure. Under this criteria, failure is mode II which we can state that as the sliding mode. In this current research paper, an experimental investigation is carried out to study the behavior of plain cement concrete beams subjected to four point loading. Three different sizes of beams with Doubly Centered Notch (DCN) are used to examine the consequence of stress intensity factor and fracture energy with diversified notch depth ratios with a constant position of the notch from a center of the beam.